Fourier-Transform Infrared Spectroscopy Analysis of 3D-Printed Dental Resins Reinforced with Yttria-Stabilized Zirconia Nanoparticles - Andrea Izabella Borș (Dentistry Journal)
Background/Objectives: This study investigates the chemical structure and molecular interactions in 3D-printed dental resins reinforced with varying concentrations of Yttria-Stabilized Zirconia (YSZ) nanoparticles, using Fourier-Transform Infrared Spectroscopy (FTIR) to assess the compatibility and bonding behavior at the molecular level. Methods: Three groups of 3D-printed methacrylate-based resin discs were fabricated: a control (0% YSZ), and experimental groups reinforced with 1% and 3% YSZ nanoparticles. Samples were produced using Digital Light Processing (DLP) technology and post-processed under standardized conditions. FTIR spectra were collected via ATR mode over a wavenumber range of 4000–600 cm−1. Spectral differences at key wavenumbers (1721.16, 1237.11, and 929.62 cm−1) were statistically analyzed using one-way ANOVA and Tukey’s post hoc test. Results: FTIR spectra showed no significant shifts in the ester carbonyl band at 1721.16 cm−1, suggesting the preservation of the core resin matrix. However, a statistically significant increase in absorbance at 1237.11 cm−1 was observed in the 1% YSZ group (p = 0.034), indicating dipolar interaction. A distinct new peak at 929.62 cm−1, corresponding to Zr–O vibrations, emerged in the 3% YSZ group (p = 0.002), confirming successful nanoparticle integration. Conclusions: YSZ nanoparticles enhance specific molecular interactions within methacrylate-based dental resins without compromising structural integrity. These findings support the potential application of YSZ-reinforced 3D-printed resins in durable, biocompatible permanent dental restorations.